Information Technology Governance Design in DevOps-Based E-Marketplace Companies Using COBIT 2019 Framework - Lestari, Merryana; Iriani, Ade; Hendry, Hendry (Universitas Nusantara PGRI Kediri, 2022)
The E-Marketplace system is a digital place where sellers and buyers meet virtually, and transactions can be processed safely. E-Marketplace companies are oriented toward consumer-centric products and services and operate and have 24/7 non-stop transaction activities. E-Marketplace system development has become the digital transformation in Information Technology (IT) governance that meets the requirements of a system-based automated control with the application of DevOps principles. This study uses a mixed method approach through questionnaires, interviews, expert judgment, and relevant literature reviews related to the e-Marketplace system and IT governance concepts using the COBIT 2019 framework, which has 11 design factors with 40 IT processes to obtain the most appropriate governance model for e-Marketplace companies. The results were obtained in the form of 6 (six) methods in the IT governance model using the DevOps approach, namely the APO03 – Managed Enterprise Architecture, APO04 – Managed Innovation, BAI04 – Managed Availability and Capacity, BAI06 – Managed IT Changes, BAI11 – Managed Projects, and DSS03 – Managed Problems with a score ≥ 75 and the capability level target is at level 4.